2013
DOI: 10.1002/jctb.4026
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and simultaneous removal of 2‐mercaptobenzothiazole and 2‐mercaptobenzoxazole from water samples by copper oxide nanoparticles

Abstract: BACKGROUND: This study introduces a method for simultaneous removal of 2-mercaptobenzoxazole (2MBO) and 2mercaptobenzothiazole (2MBT) from water samples. The method uses a cartridge loaded with copper oxide nanoparticles as an efficient adsorbent to separate these hazardous mercaptans from aqueous solutions in a flow process. RESULTS:The effects of some important parameters such as amounts of adsorbent, pH, buffer type and its volume, electrolyte concentration, contact time, flow rate, tolerable volume of solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Finally, the developed material was compared with other extraction sorbents of target analytes in environmental samples (see Table 4). Regarding aqueous samples analysis, the recovery values obtained were quite similar to those found in most reported studies; however, in certain works [23,28] these values were lower than 65%. Regarding the LODs, our values were better than those described by Parham et al [24], and similar to those reported in refs.…”
Section: Comparison With Other Commercial Sorbents and Extraction Met...supporting
confidence: 87%
See 3 more Smart Citations
“…Finally, the developed material was compared with other extraction sorbents of target analytes in environmental samples (see Table 4). Regarding aqueous samples analysis, the recovery values obtained were quite similar to those found in most reported studies; however, in certain works [23,28] these values were lower than 65%. Regarding the LODs, our values were better than those described by Parham et al [24], and similar to those reported in refs.…”
Section: Comparison With Other Commercial Sorbents and Extraction Met...supporting
confidence: 87%
“…Other advantage found is the less amount (20 mg) of sorbent required compared with single-use commercial SPE sorbents (commonly up to 150-500 mg) [28,30,31]. This amount was also similar to a nanomaterial-based method using CuNPs [23,24] probably due to surface area-to-volume ratio; however, its reusability was quite lower than that found in the present study.…”
Section: Comparison With Other Commercial Sorbents and Extraction Met...mentioning
confidence: 43%
See 2 more Smart Citations
“…Some studies on the environmental behavior and the biodegradation of MBO indicated that in environmental conditions it is very stable and cannot completely mineralized (Allaouia and Wong-WahChung 2010; Habibi and Sheibani 2012). To the best of our knowledge, very few works were reported specifically on the removal of MBO (Antonopoulou et al 2014;Habibi and Sheibani 2010;Parham and Khoshnam 2013). Hence, in aspect of established toxicity, low biodegradability and persistence of MBO in natural compartments, further work on its elimination and/or mineralization needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%